PENGARUH PAJAK PADA AKTIVITAS USAHA DAN BISNIS - Achmad Rizky Purnomo; Eriadi, Mohammad Ifandy (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
This research aims to analyze the influence of taxes on the activities of companies or businesses. Taxes are financial levies made by the government from individuals and companies to fund public services and infrastructure. In a business context, taxes have a significant impact on a company's profitability and financial health. This study examines the importance of understanding tax regulations, tax planning, and tax management in maintaining the company's financial stability. The results show that companies that manage taxes well can improve cash flow, sustainable growth, and business continuity in a competitive market. The conclusion of this study is that taxes are not only a financial burden, but also a key factor in business success. Therefore, companies need to prioritize tax compliance, develop effective tax planning strategies, and consult with tax experts to optimize financial performance.